2024
DOI: 10.3390/jmse12030374
|View full text |Cite
|
Sign up to set email alerts
|

Transient Tests for Checking the Trieste Subsea Pipeline: Toward Field Tests

Silvia Meniconi,
Bruno Brunone,
Lorenzo Tirello
et al.

Abstract: Subsea pipelines are vital arteries transporting oil, gas, and water over long distances and play a critical role in the global resource supply chain. However, they are the most vulnerable to damage from both human-made and natural causes and are characterized by inherent inaccessibility. As a result, routine inspection and monitoring technologies, both reliable and at the lowest possible cost, are needed to ensure their longevity. To fill this need, the use of transient-test-based techniques is proposed. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…In our companion paper [2], after highlighting the main issues related to fault detection in SPs, attention was focused on the Trieste (Italy) SP (Figure 1). According to the characteristics of the water supply system that includes the Trieste SP, the transient test-based techniques (TTBTs) have been identified as the most suitable approach for fault detection.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our companion paper [2], after highlighting the main issues related to fault detection in SPs, attention was focused on the Trieste (Italy) SP (Figure 1). According to the characteristics of the water supply system that includes the Trieste SP, the transient test-based techniques (TTBTs) have been identified as the most suitable approach for fault detection.…”
Section: Introductionmentioning
confidence: 99%
“…According to the characteristics of the water supply system that includes the Trieste SP, the transient test-based techniques (TTBTs) have been identified as the most suitable approach for fault detection. As described in [2], historically, Smart Pigging, Acoustic Monitoring, Remotely Operated Vehicles, and diving constitute the foundational methods for pipeline inspection. Each of these techniques is marked by significant costs and certain limitations, e.g., [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, to avoid the generation of large overpressures, the pre-transient mean velocity must be adequately small. As a consequence, small-diameter valves are used whether the pressure wave is generated by the Portable Pressure Wave Maker (PPWM) [ 42 ] or a side discharge valve [ 43 ]. Although manually operated valves can be an option, after checking the ease of the manoeuvre and therefore the speed, pneumatic-driven automatic valves are the most commonly used devices in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…Over more than half a century of development, both the technology and theory of acoustic emission have significantly improved and found extensive applications in various industries, such as civil engineering, petrochemicals, aerospace, and marine engineering [25][26][27][28][29][30][31], indicating a promising future. Meniconi, S et al [32,33] innovatively proposed a transient analysis method for fault diagnosis of underwater pipelines, which holds significant implications for the advancement of SHM techniques. Grabec I [34] simulated burst-type and continuous-type acoustic emission signals through experiments on aluminum strips and suggested that time delay estimation using the correlation method is feasible, laying the groundwork for subsequent applications of acoustic emission in pipeline leak detection.…”
Section: Introductionmentioning
confidence: 99%